FRI0396 HOW DOES OSTEOARTHRITIS PAIN IMPACT FUNCTION, MOBILITY AND REQUIREMENT FOR HELP IN DAILY ACTIVITIES IN EUROPEAN PATIENTS?. (13th June 2020) - Conaghan, P. G.; Abraham, L.; Graham-Clarke, P.; Viktrup, L.; Cappelleri, J. C.; Beck, C.; Bushmakin, A. G.; Hatchell, N.; Clayton, E.; Jackson, J.
Abstract : Background: Symptomatic osteoarthritis (OA) leads to functional limitations and loss of independence. OA management focuses on pain relief and preserving physical function using non-pharmacologic and pharmacologic therapy. Additionally, patients commonly manage OA pain by avoiding activities that exacerbate their pain. Informal care, i.e. assistance from an unpaid caregiver, plays a major role in the total care provided to patients with chronic diseases like OA. Objectives: To evaluate how OA pain severity affects physical functioning and the subsequent need for assistance with mobility and daily activities in 5 EU countries: France, Germany, Italy, Spain and UK. Methods: Data were drawn from the Adelphi OA Disease Specific Programme (2017-18), a point-in-time study of physicians and their OA patients. Patients rated their average pain intensity over the last week on a 0-10 scale (0 = no pain; 10 = worst possible pain) and were then categorised into mild (0-3), moderate (4-6) and severe (7-10) pain groups. Patients also provided an assessment of their physical function (0-10 WOMAC scale where higher scores indicated greater functional impairment), impact on mobility, whether caregiver assistance was required, daily activities requiring caregiver assistance and home modifications made due to their OA. Physicians also rated patients' functioning on a 0 to 10 scale (0 = fully functional; 10 = completely impaired). Comparisons among pain severity groups were made using chi-squared tests and analysis of variance. Results: The analysis included 1750 OA patients: 24% mild pain (n=413); 47% moderate pain (n=822); 29% severe pain (n=515). The patients were predominantly women (58%) and had a mean (SD) age of 65.6 (11.5). Increased pain severity was associated with greater functional impairment scores as reported by patients (WOMAC scores: mild pain=2.1; moderate pain=4.1; severe pain=5.9) and physician-rated functional impairment (mild pain=3.5; moderate pain=4.3; severe pain=5.6). Mobility was impacted for 78% of patients with severe pain (vs. 41% mild; 63% moderate) and the need for a walking aid such as a walking stick or walking frame increased with worsening severity; wheelchair assistance was needed for 7% of severe patients (compared with <1% of mild or moderate patients). Furthermore, 31% of patients with severe pain reported having to modify their home due to their OA (vs. 11% mild; 18% moderate [p<0.001]), typically adapting their bathroom (23%) or fitting a stairlift (6%). The need for assistance from a caregiver to help with daily activities was associated with an increase in patients' pain (9% mild; 20% moderate; 42% severe [p<0.001]). For most patients this was an immediate family member, however, the proportion of patients paying for professional care also increased with severity (1% mild; 2% moderate; 7% severe). Taking the patient to work or doctor's appointments; help with shopping; preparing/cooking meals and help with travelling out of the home were most frequently reported activities needing caregiver assistance. Conclusion: In this study of European patients, increased pain severity was associated with greater functional impairment and impact on mobility as expected; however, this study highlights the substantial need for assistance with daily activities as well as modifications to the home. The unseen costs to the patient with moderate to severe OA pain are significant. Disclosure of Interests: Philip G Conaghan Consultant of: AbbVie, BMS, Eli Lilly, EMD Serono, Flexion Therapeutics, Galapagos, GSK, Novartis, Pfizer, Speakers bureau: AbbVie, Eli Lilly, Novartis, Pfizer, Lucy Abraham Shareholder of: Pfizer, Employee of: Pfizer, Peita Graham-Clarke Shareholder of: Eli Lilly and Co, Employee of: Eli Lilly and Co, Lars Viktrup Shareholder of: Eli Lilly and Company, Employee of: Eli Lilly and Company, Joseph C Cappelleri Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Craig Beck Shareholder of: Pfizer, Employee of: Pfizer, Andrew G Bushmakin Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, Niall Hatchell: None declared, Emily Clayton: None declared, James Jackson: None declared